Liquid biopsy and preclinical tools for advancing diagnosis and treatment of patients with pancreatic neuroendocrine neoplasms. (December 2022) - Smolkova, Bozena; Kataki, Agapi; Earl, Julie; Ruz-Caracuel, Ignacio; Cihova, Marina; Urbanova, Maria; Buocikova, Verona; Tamargo, Sandra; Rovite, Vita; Niedra, Helvijs; Schrader, Joerg; Kohl, Yvonne
Abstract: Pancreatic neuroendocrine neoplasms (pNENs) are rare cancers with broad challenges for their management. The main clinical obstacles are the high rate of patients diagnosed at advanced stages, lack of prognostic markers for early detection of disease recurrence in resected patients, significant limitations in identifying those who will benefit from adjuvant therapy, and timely recognition of treatment response. Therefore, the discovery of new prognostic and predictive markers is necessary for patient stratification and clinical management. Liquid biopsy, which has revolutionized the field of clinical oncology, is extremely under-investigated in pNENs. This review highlights its potential and the recent advances in related technologies, as candidates for the delivery of the new tools that can help to refine pNEN diagnosis and to personalize treatment. In addition, the opportunities and limitations of available preclinical research models with regard to biomarker research are discussed in light of pNEN clinical needs. Highlights: Due to the rare nature and indolent biology, pNENs are significantly underinvestigated. The main clinical needs are early detection of treatment response and emerging recurrence. Liquid biopsy can deliver reliable non-invasive prognostic and predictive biomarkers. Patient-derived models can contribute to a better understanding of pNEN biology. Implementation of multi-omics technologies helps pave the way to personalized medicine.